Refractory metals revolutionizing the lighting technology: A historical review. (May 2015) - Schade, P.; Ortner, H.M.; Smid, I.
Abstract: From a historical point of view, the development of the PM processing steps and tools "for making tungsten ductile" by William D. Coolidge in 1909 marks the breakthrough for the use of tungsten filaments in the lighting industry and the beginning of the industrial era of Powder Metallurgy. However, other refractory metals, osmium and tantalum, had been considered useful lamp filaments prior to tungsten. Other technological concepts as, e.g. the gas mantle lamp of Auer von Welsbach, are still in limited use today. The significance of the Coolidge process is shortly outlined for the production of ductile tungsten. In addition some further important accompanying discoveries and inventions will be mentioned: cemented carbides and tungsten heavy metals. The scientific importance of the potassium bubbles as the strongest pinning points at highest temperatures against the movement of dislocations and grain boundaries will be highlighted shortly. It is in our opinion, the most ingenious "dispersoid" ever developed by mankind: non-effective at lower temperatures and thus not interfering with the wire drawing and coiling processes but very effective as dispersoid at the operating temperatures of incandescent lamps as mentioned above. Considering geometrical dimensions, the microstructural features of the finest wires with diameters in the single micrometer domain and the corresponding fabrication of diamond dies, necessary for the deformation of wires, also represent precursors of today's nanotechnology and micromachining. Some further important points for the fabrication of incandescent lamps are mentioned: the introduction of the Langmuir sheath and the significance of molybdenum for the lighting industry. Finally the ban of incandescent lamps by the European Union is outlined and a brief overview of modern means of lighting is given. Compact fluorescent lamps and high intensity discharge lamps and the use of refractory metals in the LED-production end this brief overview on modern lighting and no device is without a refractory metal. Highlights: Breakthrough for the production of tungsten filaments: The Coolidge Process The birth of non-sag tungsten Potassium bubbles as the most ingenious dispersoid The significace of molybdenum for the lighting industry The casual invention of hardmetals The LED-lighting revolution